Branding and/as religion: the case of Buddhist related images, semantics, and designs - Prohl, Inken (Buddhism and business, 2020)
6 Branding and/as Religion. The Case of Buddhist-Related Images, Semantics, and Designs erschien in Buddhism and Business auf Seite 111.
Gesehen am 09.12.2020